Malignant catatonia: severity, treatment and outcome: a systematic case series analysis : original investigation - Cronemeyer, Maximilian; Schönfeldt-Lecuona, Carlos; Gahr, Maximilian; Keller, Ferdinand; Sartorius, Alexander (The world journal of biological psychiatry, 2022)
Objectives: Malignant catatonia (MC) is a rare, yet potentially life-threatening neuropsychiatric condition. Evidence on its therapy is weak, treatment recommendations are scarce and predominantly unprecise. The aim of this study was to compare the effectiveness of different MC treatment approaches regarding outcome and severity of MC.Methods: We conducted systematic searches for MC case reports in biomedical databases and the psychiatric archive of University Hospital Ulm. Treatments were compared considering MC severity and temporal aspects.Results: A total of 117 cases were included. Treatment had a significant influence on outcome: treatment with both benzodiazepines and electroconvulsive therapy (ECT) entailed the most favourable, purely supportive therapy the least favourable outcome. Earlier application of benzodiazepines was significantly associated with a favourable outcome. A classification of MC severity was developed. Patients with severe MC were significantly more often subject to intensive care treatment and had a 78% higher risk of dying than in moderate MC.Conclusions: This is the first study to introduce a severity classification for MC, and the largest to compare outcomes of MC treatments with clear distinction from neuroleptic malignant syndrome (NMS). Preferable MC treatment should include early initiation of benzodiazepines and ECT. MC severity could serve as a prognostic instrument.